Political Economy of Migrant Health Care in the Czech Republic - Pěničková, Daniela (Lidé města, 2014)
The present time is marked by flux in the conceptualization of social relations and the organization of health care. The last couple of decades have witnessed fundamental changes in health insurance systems worldwide. Despite the fact that Western European countries have experienced an unexpected number of problems with their systems of social insurance combined with the private sector, the post-communist countries have largely followed the suit of adopting private-sector reforms to their formerly socialist health care systems while keeping the concept of national health care. However, the private health care policies adopted by some of the post-socialist governments directly breach basic human rights and are in conflict with the current EU non-discriminatory principle of foreign law. They are, in fact, conceptualized as primary boosters not for private but for national economies. In the Czech Republic this tendency is played out by state policies towards migrants from non-EU countries. While general health insurance is available to all EU citizens and migrants with permanent residency, migrants from non-EU countries who do not have the status of an employee or who are students not covered by international agreements are excluded from participation in the Czech national health care system. Drawing on the author’s ethnography carried out among Russian-speaking migrant parents living in the Czech Republic and on case studies and information gathered by the Consortium of Migrants Assisting Organizations in the Czech Republic (of whom the author is a member), this contribution opens a crucial debate on the process of individual responsibility for health becoming enmeshed with privatization and commodification of health care based on ethnicity and migrant status.